PENERAPAN ALGORITMA KLASIFIKASI NEAREST NEIGHBOR (K-NN) UNTUK MENDETEKSI PENYAKIT JANTUNG - MEI LESTARI (Faktor Exacta, 2014)
Data from WHO states that 7,3 million people die because of Heart Disease. Although Heart Disease is not contagious, this kind of disease is the number 1 disease causing death. Heart disease is also called as coroner disease. It happens when the blood drifting to the heart muscles stops so that it causes heart disorder (Rajkumar & Reena, September 2010). The application of Nearest Neighbor classification (K-NN) algorithm is expected to overcome the problems on the affectivity and accuracy in detecting heart disease. In this research, the K-NN with K = 9 is used on 100 patients of heart disease. The result revealed is that the accuracy is 70% and the AUC is 0.875 which belong to the good classification. Hence, K-NN algorithm can be used and applied in detecting heart disease. Keywords: Nearest Neighbor, Jantung, Algoritma, Akurasi.